(untitled) (Revista Contexto & Saúde, 2025)
Objective: Identify possible facilitators or barriers to collaborative interprofessional care in primary health care and its relationship with safe care. Method: This is an exploratory qualitative study using a focus group technique with family health teams from a municipality in the interior of São Paulo. The inclusion criterion was to have been part of the team for at least six months. The exclusion criterion was being on vacation or absent during the data collection. A script with guiding questions about collaborative interprofessional practices and safe care was used. The transcript was processed using IRAMUTEQ software and analyzed considering the theoretical framework of collaborative interprofessional practices and safe care. Results: Six classes were formed: implementation of safe care, work objectives, decision-making, care construction, team communication, and actions that integrate safe care. How each member performs their role, their understanding of work objectives, communication, how care is provided, and how team disagreements are handled are reflected in work performance and resolution. Conclusion: Thus, factors related to safe care and team climate, such as job satisfaction, are influenced by how the team interacts daily.